2018
DOI: 10.1016/j.agrformet.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation events reduce soil respiration in a coastal wetland based on four-year continuous field measurements

Abstract: Coastal wetlands are considered as a significant sink for global carbon because their organic-rich soils. Given exposed to shallow water tables, water from groundwater is transported upward to the root zone through capillary rise, thus soil moisture in coastal wetlands is relatively high even when there is no precipitation. We expected that as precipitation occurred, the soils in coastal wetlands might become quickly saturated and lead to the development of anoxic conditions. We further hypothesized that such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 80 publications
2
66
1
Order By: Relevance
“…Previous study has demonstrated that the average annual precipitation has decreased with a rate of 4.5 mm yr -1 and the annual air temperature has increased by 1.7°C over the past 55 years in the YRD [28]. This shift of precipitation and air temperature might induce drier and hotter seasons in the YRD in the future, which has a great possibility to increase ER, thus greater C loss from this coastal wetland.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous study has demonstrated that the average annual precipitation has decreased with a rate of 4.5 mm yr -1 and the annual air temperature has increased by 1.7°C over the past 55 years in the YRD [28]. This shift of precipitation and air temperature might induce drier and hotter seasons in the YRD in the future, which has a great possibility to increase ER, thus greater C loss from this coastal wetland.…”
Section: Discussionmentioning
confidence: 97%
“…Microbiological processes and the roles of microorganisms could be another reason for the variation in ecosystem CO 2 and CH 4 rates. Their activities are controlled by several biological, chemical, and physical factors in soil [19,20,22,28,29,44]. Therefore, soil properties including soil organic carbon (SOC), total nitrogen (TN), inorganic nitrogen, total phosphorus (TP), available phosphorus (AP), salinity, and pH are closely related to CO 2 and CH 4 fluxes [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coastal wetlands are considered a significant sink for global carbon [30], and Xie et al [31] reported that alkaline/saline soils can absorb CO 2 at a rate of 0.3-3.0 μmol m -2 s -1 with an inorganic, non-biological process. However, unlike these earlier studies, our research has shown that the mean soil respiration of growing seasons in salinized bare land was 0.59 μmol m -2 s -1 , which is similar to the observations of Lai et al [32], who found negative soil respiration only when the temperature was below 5ºC in natural ecosystems of saline/alkaline soils.…”
Section: Discussionmentioning
confidence: 99%